A WiMAX Payload for High Altitude Platform Experimental Trials. (26th June 2008) - Thornton, John; White, Andrew D.; Tozer, Tim C.
Abstract : The Swiss-based "StratXX" project during 2006-2007 has been developing a stratospheric lighter-than-air platform for deployment of telecommunications and environmental monitoring services. In support of a first round of experimental trials, a WiMAX communications subsystem, including platform payload and ground stations, has been developed. The communications system design and results of terrestrial pretrials are reported.